2017
DOI: 10.1007/s00425-017-2712-x
|View full text |Cite
|
Sign up to set email alerts
|

Different exogenous sugars affect the hormone signal pathway and sugar metabolism in “Red Globe” (Vitis vinifera L.) plantlets grown in vitro as shown by transcriptomic analysis

Abstract: Exogenously applied 2% fructose is the most appropriate carbon source that enhances photosynthesis and growth of grape plantlets compared with the same concentrations of sucrose and glucose. The role of the sugars was regulated by the expression of key candidate genes related to hormones, key metabolic enzymes, and sugar metabolism of grape plantlets ( Vitis vinifera L.) grown in vitro. The addition of sugars including sucrose, glucose, and fructose is known to be very helpful for the development of grape (V. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…Changes in sugar concentrations in plant tissues affect the expression of nuclear and plastid genes, although the latter generally react to sugars quite slowly [10,29,36]. Studies using DNA microarrays demonstrated both the stimulation and inhibition of several hundred different genes in response to exogenously administered glucose and sucrose, or sugar depletion, including regulation of transcription factors [20,22,29,46,69]. Glucose-regulated genes are involved in all the metabolic and growth processes, and in responses to stress factors [23].…”
Section: Introductionmentioning
confidence: 99%
“…Changes in sugar concentrations in plant tissues affect the expression of nuclear and plastid genes, although the latter generally react to sugars quite slowly [10,29,36]. Studies using DNA microarrays demonstrated both the stimulation and inhibition of several hundred different genes in response to exogenously administered glucose and sucrose, or sugar depletion, including regulation of transcription factors [20,22,29,46,69]. Glucose-regulated genes are involved in all the metabolic and growth processes, and in responses to stress factors [23].…”
Section: Introductionmentioning
confidence: 99%
“…Many transcriptional factors expressed under Cd stress have been reported in previous studies, such as NAC, bHLH, WRKY, etc [35,36,37]. In this study, many unreported transcriptional factors were discovered, such as C3H, C2H2, Orphans, and MYB, etc, whereas C2H2 has been previously reported associated with osmotic stress in Arabidopsis thaliana [38].…”
Section: Resultsmentioning
confidence: 57%
“…The ratio of ABA quantity to GAs quantity in seeds or any other plant tissue that has capability of being dormant has been reported to be the determinant factor of the seed or tissue dormant status [7], and the effect of this factor (ABA/GAs ratio) surpasses the effect of any other factors and molecular processes that regulate dormancy in plant system. In maize, CYP01A26 was reported to exhibit ent-kaurene oxidase activity which led to increased accumulation bioactive GAs and consequently result in early seed dormancy break [128,129] Similarly, in rice, 13-hydroxylation pathway that involves the activity of 13-hydroxlases which were coded by CYP714b1 and CYP714B2 genes led to early seed germination [130]. We therefore infer that the activities of CYP1A2, CYP2C, CYP2J, CYP2EI, CYP3A4, found in linoleic acid metabolic pathway might have led to increase biosynthesis of GAs and activities of GAs in the tubers, led to dormancy break.…”
Section: Pathways Elucidationsmentioning
confidence: 99%